2007
DOI: 10.1007/s10930-007-9094-z
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and Biological Characterization of Two Crotamine Isoforms IV-2 and IV-3 Isolated from the Crotalus durissus cumanensis Venom

Abstract: In this work, we isolated the two new crotamine isoforms from the Crotalus durissus cumanensis rattlesnake venom and its "in vitro" neurotoxic, myotoxic and lethality (DL(50)) intracerebroventricular (i.c.v.) effects were characterized. These proteins were named IV-2 and IV-3 and were purified by combination of two chromatographic steps on molecular exclusion chromatography on Superdex 75 and reverse phase HPLC (mu-Bondapack C18). The molecular mass of the crotamine isoforms was 4905.96 Da for isoform IV-2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
4
8
0
2
Order By: Relevance
“…The purification procedure for basic PLA 2 s developed by Ponce-Soto et al [6, 15, 23, 24] showed to be also efficient for the obtainment of the Bothropsroedingeritoxin I PLA 2 (BrTX-I) from Bothrops roedingeri snake venom. Fractionation protocol of this crude venom using a single pass chromatographic in a column μ -Bondapack C-18 coupled to a system of reverse phase HPLC (0.78 cm–30 cm; Waters 991-PDA system) gave rise to 15 fractions at 280 nm, the eight last being the basic PLA 2 named BrTX-I (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The purification procedure for basic PLA 2 s developed by Ponce-Soto et al [6, 15, 23, 24] showed to be also efficient for the obtainment of the Bothropsroedingeritoxin I PLA 2 (BrTX-I) from Bothrops roedingeri snake venom. Fractionation protocol of this crude venom using a single pass chromatographic in a column μ -Bondapack C-18 coupled to a system of reverse phase HPLC (0.78 cm–30 cm; Waters 991-PDA system) gave rise to 15 fractions at 280 nm, the eight last being the basic PLA 2 named BrTX-I (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of BrTX-I to induce edema was studied in groups of five Swiss mice (18–20 g) according Ponce-Soto et al [6, 23, 24]. Twenty microliters of phosphate-buffered saline (PBS; 0.12 M NaCl, 0.04 M sodium phosphate, pH 7.2) with BrTX-I (1, 5, 10 and 20  μ g/paw) were injected in the subplantar region of the right footpad.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crotalus durissus cumanensis (CDCm) is a snake found in Venezuela and northern Brazil, and its venom contains enzymes and toxins such as crotoxin, crotamine, gyroxin and convulxin (10,11). Crotoxin, the major component of the C. d. cumanensis venom (CDCmV), is responsible for most of its neurotoxic and myotoxic effects (6,12).…”
Section: Introductionmentioning
confidence: 99%